The Effects of Accent Familiarity on English as a Foreign Language Students’ Word Recognition and Comprehension of the English Language - White, Alan Robert; Treenate, Dhunyawat; Kiatgungwalgrai, Arunee; Somnuk, Rachapon; Chaloemchatvarakorn, Kitti (วารสารวิจัย มทร. กรุงเทพ, 2016)
Tests and in class assessments of EFL (English as a foreign language) listening comprehension generally attempt to sample from language that reflects what students will be expected to comprehend in the relevant contexts. Unfortunately, most listening tests and assessments do not consider or address the issue of accented English in ESL listening. This study examined the issues and problems EFL students face when listening to unfamiliar accents. Three groups (n=99) of Bachelor of Arts English major students enrolled at Rajamangala University of Technology Krungthep, Bangkok, Thailand were exposed to various accents at different frequency levels throughout the Advanced Listening and Speaking course. Tests were conducted to establish whether accent familiarity affected students’ understanding of the English language. The results of the tests suggest that familiarity of an accent can aid listener comprehension.